2018
DOI: 10.1007/s00404-018-4853-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a cervical dysplasia and its treatment on quality of life and sexual function

Abstract: Data suggest that women with the diagnosis of a cervical dysplasia are impaired in their sexual function as well as general and cervix-related quality of life, mostly independent of conization or further observation. To improve salutogenesis in the long run, the communication on dysplasia and its treatment strategy at the beginning, as well as part of aftercare, or psychosomatic intervention, might be treatment options for women at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…In non-cleared patients, our study showed a slight worsening of anxiety status and sexual function as shown by STAI-Y scores and FSFI scores before and after cervical treatment. These results are comparable to the results reported in the literature for which sexual dysfunction was seldom impacted by conization ( 53 ), but it was more related to the status of the cervical dysplasia and HPV infection rather than surgical treatment at the cervical level ( 54 ).…”
Section: Discussionsupporting
confidence: 87%
“…In non-cleared patients, our study showed a slight worsening of anxiety status and sexual function as shown by STAI-Y scores and FSFI scores before and after cervical treatment. These results are comparable to the results reported in the literature for which sexual dysfunction was seldom impacted by conization ( 53 ), but it was more related to the status of the cervical dysplasia and HPV infection rather than surgical treatment at the cervical level ( 54 ).…”
Section: Discussionsupporting
confidence: 87%
“…The age of women ranged from 25 to 69 years [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]; most were married [1,2,9,18,20,21,24,25,27] and lived in the United States, Germany, or Belgium [9,[15][16][17][18]20,21,23,25]. The types of cancers analyzed in women with sexual dysfunctions were breast, cervical, endometrial, ovarian, vulvar, and gynecological [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. Additionally, women with cancer were treated with surge...…”
Section: Resultsmentioning
confidence: 99%
“…The types of cancers analyzed in women with sexual dysfunctions were breast, cervical, endometrial, ovarian, vulvar, and gynecological [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. Additionally, women with cancer were treated with surgery, chemotherapy, radiotherapy, or hormonal therapy [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. The follow-up time ranged from six months to five years [16][17][18][19][20][21][22][23]25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanama, enfeksiyon, servikal stenoz gibi nadir görülen komplikasyonlar görülebilmektedir (4) . Reprodüktif çağdaki kadınlarda seksüel aktif dönemde yapılan LEEP kadın psikoseksüel fonksiyonlarını da etkileyebilmektedir (5)(6)(7)(8)(9)(10) .…”
Section: Introductionunclassified